Investigating the Combined Impact of Microlearning and Spaced Repetition on EFL Learners’ Vocabulary Retention - Durotunnasihah Durotunnasihah; Iis Sujarwati; Kasmaini Kasmaini (Journal of Education and Teaching Learning, 2026)
Vocabulary retention is a persistent challenge in EFL learning, often limited by insufficient exposure and reliance on rote memorization. Although microlearning and spaced repetition have been studied individually, few investigations have examined their combined effect on vocabulary retention and learning experience. By using quantitative design, this study explored the impact of microlearning integrated with spaced repetition on EFL students’ vocabulary mastery, retention, and perceptions. Forty-six beginner-level EFL students in Bengkulu participated in pre-test, post-test, and delayed post-test assessments, complemented by questionnaires, analyzed using repeated-measure ANOVA. The results indicated significant improvement from pre-test to post-test, stable or slightly increased scores in the delayed post-test, and high learner satisfaction. These findings suggest that repeated and manageable exposure effectively strengthen retention. Overall, integrating microlearning with spaced repetition enhances vocabulary learning and long-term retention, providing practical guidance for designing short, repeated, and engaging learning experiences in EFL contexts. Future research should involve larger and more diverse participant groups, extend intervention and retention periods, incorporate qualitative methods to explore learners’ experiences, and compare alternative instructional approaches to further clarify the effectiveness of this combined strategy.